The protective role of (−)-epigallocatechin-3-gallate in thrombin-induced neuronal cell apoptosis and JNK-MAPK activation. Issue 7 (6th May 2015) - He, Qianqian; Bao, Lei; Zimering, Jeffrey; Zan, Kun; Zhang, Zuohui; Shi, Hongjuan; Zu, Jie; Yang, Xinxin; Hua, Fang; Ye, Xinchun; Cui, Guiyun
Abstract : (−)-Epigallocatechin-3-gallate (EGCG), the major polyphenolic component of green tea, has anti-inflammatory and antioxidant properties and provides neuroprotection against central nervous system diseases. Yet, it is not known whether EGCG may be neuroprotective against intracerebral hemorrhage. In this study, we used a simplified in-vitro model of thrombin neurotoxicity to test whether EGCG provides neuroprotection against thrombin-associated toxicity. Exposure of primary cortical neurons to thrombin (100 U/ml) caused dose-dependent and time-dependent cytotoxicity. Cell Counting Kit 8 and lactate dehydrogenase were used to monitor cell viability after exposure of neurons to thrombin or EGCG and after EGCG pretreatment. Flow cytometric analysis and western blotting demonstrated that thrombin-induced neuron degeneration occurs through apoptosis. A concentration of 25 μM EGCG significantly abolished thrombin-induced toxicity and prevented apoptosis by suppressing c-Jun-N-terminal kinase (JNK) phosphorylation, and the JNK inhibitor SP600125 reduced thrombin-induced caspase 3 activation and apoptosis. These data suggest that EGCG may have protective effects against thrombin-induced neuroapoptosis by inhibiting the activation of JNK, leading to caspase 3 cleavage. EGCG is a novel candidate neuroprotective agent against intracerebral hemorrhage-induced neurotoxicity.